PENGEMBANGAN MEDIA PRAKTIKUM HUKUM OERSTED - Hardianto, Firman (Jurnal Sains dan Pendidikan Fisika, 2021)
Based on the results of survey by Ivan et al (2015), 73,3% of students and theacers think that the magnetic field is difficult material to understand. For this reason, practicum media are needed to facilitate understanding of magnetic field. Researcher was made a media tool for Oersted law practice with such development compared to existing tools. The methods used include starting from design, build, and media tool test. The results obtained already have novelty, but there are still some deficiency that can become the basis for researcher to redevelop similar tools by fixing existing deficiencies.